Comparison of post‐stent optical coherence tomography findings among three subtypes of calcified culprit plaques in patients with acute coronary syndrome. Issue 4 (17th March 2020) - Nakajima, Akihiro; Araki, Makoto; Kurihara, Osamu; Minami, Yoshiyasu; Soeda, Tsunenari; Yonetsu, Taishi; Crea, Filippo; Takano, Masamichi; Higuma, Takumi; Kakuta, Tsunekazu; Adriaenssens, Tom; Lee, Hang; et al.
Abstract: Objectives: To compare the postprocedural optical coherence tomography (OCT) findings and in‐hospital outcomes among the three subtypes of calcified plaques: eruptive calcified nodules, superficial calcific sheet, and calcified protrusion. Background: Recently, three subtypes of calcified culprit plaques were reported in patients with acute coronary syndrome (ACS). How these subtypes respond to stenting is unknown. Methods: ACS patients with calcified plaque at the culprit lesion were selected from our database. OCT findings at baseline and after stent implantation were compared. Results: In the final analysis, 87 cases were included. Preprocedural OCT showed eruptive calcified nodules in 19 (21.8%) cases, superficial calcific sheet in 63 (72.4%), and calcified protrusion in 5 (5.7%). Stent edge dissection (SED) and incomplete stent apposition (ISA) were frequently observed in the eruptive calcified nodules group compared to superficial calcific sheet or calcified protrusion (SED; 47.4% vs. 17.5% vs. 20.0%; p = .032, ISA; 94.7% vs. 58.7% vs. 0.0%; p < .001). The superficial calcific sheet group had the smallest minimal stent area (MSA) among the three groups (eruptive calcified nodules vs. superficial calcific sheet vs. calcified protrusion: 6.29 ± 2.41 vs. 4.72 ± 1.37 vs. 6.56 ± 1.13; p = .007). The superficial calcific sheet group had a higher rate of periprocedural myocardial infarction compared to the eruptive calcified nodules group (60.3% vs. 31.6%; p = .028). Conclusions: This study demonstrated eruptive calcified nodules are associated with higher incidence of SED and ISA, whereas superficial calcific sheets are associated with small MSA and higher periprocedural myocardial infarction.